Nanotechnology-based theranostics for bone tumors - Wenwen Zhan; Shuyan Zeng; Lin Yang; Ye-Zhong Zhang; Jing Zhang (Giant, 2025)
Bone tumors, particularly osteosarcoma and metastatic lesions, present significant challenges in current diagnostic and therapeutic approaches, often failing to meet patients’ expectations for quality of life. Recent rapid advancements in nanotechnology have introduced diverse and more effective strategies for the management of bone tumors. This review comprehensively examines the applications of nanomedicine in bone oncology, with a focused discussion on emerging developments and future prospects in imaging modalities, image-guided therapies, and targeted therapeutics. Each section critically evaluates the strengths and limitations of existing diagnostic and treatment protocols, aiming to provide innovative perspectives and methodologies for clinical management of bone tumors. The synthesis of these insights seeks to bridge current technological gaps and advance precision medicine in musculoskeletal oncology.